2022
DOI: 10.21037/qims-22-378
|View full text |Cite
|
Sign up to set email alerts
|

Development and internal validation of a conventional ultrasound-based nomogram for predicting malignant nonmasslike breast lesions

Abstract: Background: The aim of this study was to develop a conventional ultrasound (US) features-based nomogram for the prediction of malignant nonmasslike (NML) breast lesions.Methods: Consecutive cases of adult females diagnosed with NML breast lesions via US screening in our center from June 1 st , 2017, to April 17 th , 2020, were retrospectively enrolled. Candidate variables included age, clinical symptoms, and the image features obtained from the conventional US. Nomograms were developed based on the results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Compared with IDC, the size of SA nodules is smaller, and SA does not clinically manifest symptoms, thereby complicating palpation and preoperative ultrasonic diagnosis. Therefore, this ultrasound-based comparative study between SA and IDC enabled the construction of a nomogram to assist ultrasound physicians in not only further analyzing the value of various ultrasonic features in SA diagnosis but also calculating the total score on the nomogram to predict the risk of SA (17)(18)(19). Our research indicated that age, nodule size, menopausal status, presence of clinical symptoms, palpability of lesions, margins, internal echo, CDFI grading, and RI could be used as predictive factors for distinguishing between SA and IDC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with IDC, the size of SA nodules is smaller, and SA does not clinically manifest symptoms, thereby complicating palpation and preoperative ultrasonic diagnosis. Therefore, this ultrasound-based comparative study between SA and IDC enabled the construction of a nomogram to assist ultrasound physicians in not only further analyzing the value of various ultrasonic features in SA diagnosis but also calculating the total score on the nomogram to predict the risk of SA (17)(18)(19). Our research indicated that age, nodule size, menopausal status, presence of clinical symptoms, palpability of lesions, margins, internal echo, CDFI grading, and RI could be used as predictive factors for distinguishing between SA and IDC.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, microcalcification is an essential manifestation of mammography. Earlier studies have reported that 20-40% of SA lesions exhibit microcalcification, and the morphology and distribution of microcalcification are comparable to malignant tumors (5,10,19). In a breast ultrasound examination, SA lesions with microcalcification are more susceptible to being classified by ultrasound physicians as BI-RADS level 4 or higher.…”
mentioning
confidence: 97%
“…No gold-standard approach is currently available for the calculation of the sample size requirements of risk prediction models. However, it is widely accepted that at least 10 events per candidate variable for the logistic regression analysis are needed for the derivation of a risk prediction model ( 13 ). As 22 candidate variables were included in the multivariable regression analysis, at least 220 lesions were required for this study.…”
Section: Methodsmentioning
confidence: 99%
“…All images included at least 2 orthogonal planes (radial and antiradial planes or transverse and longitudinal planes). According to the ACR BI-RADS fifth edition classification criteria and a previous study (15), all images were analyzed retrospectively by two breast radiologists (reader 1 with 10 years' experience and reader 2 with 5 years' experience). The radiologists strictly recorded 15 ultrasonic features, as follows: orientation, shape, echogenic pattern, margin, posterior features, calcifications, vascularity grade, vascularity distribution, background echotexture of parenchyma (BEP), anteroposterior thickness of breast parenchyma (TBP), anteroposterior thickness ratio of breast parenchyma to tissue before pectoralis fascia (RPT), anteroposterior thickness ratio of breast parenchyma to mammary fat (RPF), lymph node metastasis, tumor size, and BI-RADS category.…”
Section: Clinical Characteristic Acquisition Ultrasonic Image Acquisi...mentioning
confidence: 99%